A lifestyle educational course as an adjunct to biologic administration in patients with severe asthma: A feasibility study - Joseph W. Lanario; Drew Davies; Lucy Cartwright; Michael E. Hyland; Matthew Masoli (PEC Innovation)
Objective: To assess the feasibility and acceptability of adapting a psychoeducation course (Body Reprogramming) for severe asthma and finding suggestions for improvement. Methods: Severe asthma patients were recruited from a single centre and enrolled in an online group-based course. Each course consisted of four sessions: introduction to BR, stress, exercise, and diet. Participants were asked to complete questionnaires assessing HRQoL, mood, asthma and extra-pulmonary symptoms, pre/post course. Those who attended two or more sessions were invited to provide feedback in interviews. Results: Twenty-eight participants took part in one of the five courses. Thirteen (46 %) attended all four sessions and were sent post-course questionnaires, eight participants (62 %) returned them. Twelve participants provided post course feedback, Themes included: The course as a time to reflect, Appreciation of the group-format, Impact of pre-existing knowledge on enjoyment of the course and Areas of improvement. Maintaining course size, clarification of the course aims and methods were identified as areas of improvement by participants. Conclusion: An educational course focused on managing extra-pulmonary symptoms is feasible and of perceived benefit to patients with severe asthma. Innovation: BR could be incorporated into a rehab programme for patients with severe asthma with significant extrapulmonary symptoms.